HabiFab a relocatable industry 5.0 prefabrication facility for hybrid housing components with integrated transitional housing - Juria, Oliver Jaison D.; David Xander T. Lacson (Quezon City College of Architecture, University of the Philippines Diliman, 2025)
Rapid urbanization in Metro Manila led to increased demand for housing, straining the capacity of traditional construction methods and creating a 6.8 million-house backlog. There is a lack of adequate production facilities for housing components in the Philippines resulting in housing challenges related to affordability and sustainability . The study proposes an architectural design of a Relocatable Industry 5.0 Prefabrication Facility for Hybrid Housing Components with Integrated Transitional Housing that enables 21st Century Urban Regeneration in the Philippines. The Prefabricaton Facility involves the production of steel, precast concrete, and 3d printed concrete, to create customizable housing components. The proposed mixed-use zoning integrates transitional housing, providing temporary shelter for those transitioning into permanent housing for slum upgrading approaches. By adopting Industry 5.0 principles, this design project aims to create a human-centered and technologically advanced facility that promotes mass customization. A combination of literature review, interviews, and case studies were employed to gather data for the lack of architectural framework and guidelines in the field of housing supply chains and Industry 5.0. This information was used to develop spatial and process analysis maps, which informed the architectural program and system for the creation of the proposed design’s form and function. The proposed 2.07-hectare site is located in the Fairview Community District of Commonwealth, Quezon City. Adjacent to dense informal settlements, this underutilized government land, which is designated for future development by the DHSUD, offers high accessibility, making it an ideal location for the study’s facility. The proposal aims to regenerate the surrounding neighborhood by providing affordable housing solutions and job opportunities. The design of the facility is based on the analysis of production lines processes, informal settlement family
Include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Emergency housing -- Quezon City; Prefabricated houses -- Quezon City; Buildings, Prefabricated -- Quezon City; Urban renewal -- Quezon City